Does the Office of the Prime Minister in Uganda conduct Gender Responsive Evaluations? - Namara, Rose B. (African Journal of Governance and Development, 2018)
Gender equality and women’s empowerment are possible when development programmes and policies confront unfair power relationships between men and women. Monitoring and evaluation are tools that can enhance gender responsiveness and/or conceal gender inequalities. This paper analyzed whether the 2016 process evaluation of the Universal Primary Education programme (UPE) undertake by Office of the Prime Minister (OPM) was gender responsive. The critical review of the evaluation report show that OPM did not set out to undertake a gender responsive evaluation though the UPE programme by design was gender responsive. This enabled a generic evaluation to highlight findings on some gender indicators embedded in the programme, though the report was silent on other issues like; early pregnancy, absenteeism and school drop out for girls due to gender roles and cultural beliefs. The evaluation used a generic evaluation methodology, the objectives did not require a gender responsive study, there was no requirement of a gender responsive evaluation team and the design did not specify that some of data sources include women and other vulnerable groups. The evaluation process was not necessarily taken to be a social change process for enhancing learning and empowerment of stakeholders
Keywords: Gender Responsive; Monitoring and Evaluation; Gender Empowerment